The effect of phloretin on synaptic proteins and adult hippocampal neurogenesis in Aβ (1‐42)‐injected male Wistar rats. (23rd April 2018) - Ghumatkar, Priya; Peshattiwar, Vaibhavi; Patil, Sachin; Muke, Suraj; Whitfield, David; Howlett, David; Francis, Paul; Sathaye, Sadhana
Abstract: Objectives: Considering the deleterious effect of Aβ1‐42, a study was designed to evaluate the effect of phloretin on altered synaptic proteins and adult hippocampal neurogenesis in Aβ1‐42‐injected Wistar rats. Methods: The rats were pretreated with 5 mg/kg p.o dose of phloretin and donepezil (positive control) for 28 days, followed by intrahippocampal injections of aggregated Aβ1‐42. After termination, perfused brains were isolated and subjected to Western blot and immunohistochemistry (IHC) analysis. Key findings: The Western blot revealed that Aβ1‐42‐injected rats had significantly low levels of synaptophysin as compared to sham control. Phloretin pretreatment significantly protected the presynaptic protein synaptophysin against the effects of Aβ1‐42. There were no significant changes in the levels of PSD95 between different groups. The IHC findings showed that Aβ1‐42 significantly reduced the Ki67 and DCX in the dentate gyrus as compared to sham control. However, phloretin significantly improved the number of Ki67‐ and DCX‐positive neurons in the dentate gyrus region as compared to Aβ1‐42 group. Conclusions: This study demonstrated the protective effect of phloretin on synaptophysin and adult neuronal proliferating cells in Aβ1‐42‐injected rats. The encouraging findings highlight the potential of phloretin as a dietary supplement targeting key therapeutic mechanisms in neurodegenerative disorders such as AD.